A kind of refractory high-strength coke oven mud and preparation method thereof

By modifying the combination of high-temperature clay, heat-resistant aggregate and inorganic adhesive, the problem of insufficient high-temperature resistance and strength of existing coke oven mud is solved, and the mechanical strength, impact resistance and high-temperature resistance of coke oven mud are achieved. The significant improvement of the coke oven mud is formed that is refractory, high-strength, low-strength, acid-resistant and thermal shock-resistant.

CN119038953BActive Publication Date: 2025-02-11LINHUAN COKING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411524316.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing coke oven mud needs to be further improved in terms of high temperature resistance and strength, and the composition is too simple, and lacks the improvement of the fire resistance of auxiliary materials to the materials.

Method used

Using a combination of modified high-temperature clay, heat-resistant aggregate and inorganic adhesive, the preparation method of modified high-temperature clay, including the mixing of ultra-fine calcined kaolin, silicon micro powder and silicone particles and high-temperature calcination, is prepared with excellent resistance to Modified high-temperature clay with high temperature performance. At the same time, the silicon carbide fibers are modified by thermal isostatic treatment to form a dense heat-resistant aggregate structure, and a silicon gel is prepared by hydrolysis of the silicon source, and an aluminum phosphate structure is introduced to enhance the adhesive ability of the inorganic adhesive.

Benefits of technology

The mechanical strength, impact resistance and high temperature resistance of coke oven mud have been significantly improved, forming a coke oven mud that is refractory, high strength and low, acid-resistant and thermal shock-resistant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038953B_ABST
    Figure CN119038953B_ABST
Patent Text Reader

Abstract

The invention discloses a fire-resistant and high-strength coke oven mud and a preparation method thereof, belonging to the technical field of mud processing, and is used to solve the technical problem in the prior art that the high-temperature resistance and strength of the coke oven mud need to be further improved. The invention ensures the compatibility between the systems by preparing silicon-based modified high-temperature clay, heat-resistant aggregate and inorganic adhesive, and the stability of the silicon-oxygen structure provides the system with extremely excellent high-temperature resistance and acid resistance. After the modified silicon nitride fiber is subjected to hot isostatic pressing treatment, the heat-resistant aggregate obtained by atomic rearrangement has an extremely excellent spatial structure, which significantly improves the mechanical strength of the material as a skeleton. In addition, the inorganic adhesive obtained by introducing an aluminum phosphate structure in the process of preparing silica gel has excellent high-temperature bonding ability. The three are combined with auxiliary materials to obtain a coke oven mud with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mud processing, and in particular to a fire-resistant and high-strength coke oven mud and a preparation method thereof. Background Art

[0002] Coke oven mud is a special material used in the coking process to repair and seal cracks and joints in coke ovens to ensure the airtightness and structural integrity of the furnace body. Early coke oven mud was mainly based on clay, mixed with lime and water. This material performed generally well in terms of heat resistance and strength, and dried slowly, which could easily lead to prolonged maintenance time. Subsequently, the industry began to introduce chemical adhesives such as phosphates and silicates, which significantly improved the high temperature resistance and mechanical strength of the mud. In modern times, coke oven mud uses high-tech materials such as ceramic fibers and special resins, which provide coke oven mud with more outstanding comprehensive performance.

[0003] Prior art CN85109463A discloses a high-strength coke oven mud, which includes three solid components: 25-88% SiO2, 6-65% Al2O3 and 4-12% P2O5. In order to ensure such high tensile strength, other solid components must be kept at the lowest value possible, generally below 4%, preferably below 2%; it is used for stacking silica bricks for the coke oven wall structure. When baked to the usual coke oven temperature (about 1100°C), not only does the mud body have high tensile strength, but it also adheres to the silica bricks. The tensile strength of the binder exceeds the tensile strength of the silica bricks.

[0004] However, the above patent content is to mix SiO2, Al2O3 and P2O5 to obtain the solid components of high-strength coke oven mud. However, the solid components of the mud obtained by mixing solid particles alone are too brittle after solidification due to the lack of a skeleton structure inside to fill the microscopic gaps. As a result, its impact resistance and strength need to be further improved. In addition, the composition is too simple and there is a lack of auxiliary materials to improve the fire resistance of the material, which ultimately leads to the need to further improve the strength and high temperature resistance of the material.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a refractory and high-strength coke oven mud and a preparation method thereof, so as to solve the technical problem in the prior art that the high temperature resistance and strength of the coke oven mud need to be further improved.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A fire-resistant and high-strength coke oven mud comprises the following raw materials in parts by weight: 30-50 parts of modified high-temperature clay, 20-40 parts of heat-resistant aggregate, 5-15 parts of inorganic adhesive, 10-25 parts of silica sand, 5-15 parts of water glass and 1-5 parts of steel fiber;

[0009] The preparation method of modified high temperature clay comprises the following steps:

[0010] A1. Mix ultrafine calcined kaolin, silicon powder and silicone particles evenly and press them into shape. After natural air drying for 1-2 hours, place them in an oven and bake them for 2-4 hours to obtain prefabricated clay.

[0011] A2. Add the prefabricated clay into a tubular furnace and calcine it at high temperature to obtain modified high-temperature clay.

[0012] The reaction equation for preparing modified high-temperature clay is: 2Al2O3+SiO2→Al2O3·SiO2

[0013] Reaction principle for preparing modified high-temperature clay: Kaolin is mainly composed of kaolinite Al2Si2O5(OH)4, which will decompose at high temperature and react with silicon dioxide in silicon micropowder to cross-link and form a more stable cross-linked structure.

[0014] Furthermore, in step A1, the dosage ratio of ultrafine calcined kaolin, silicon micropowder and silicone particles is 75-80g:15-20g:5-8g, and the temperature of the oven is 100-150°C; in step A2, the operation of high-temperature calcination is: after nitrogen protection is introduced, the tubular furnace is heated to 1400-1600°C at a heating rate of 5°C / min, and the temperature is kept for calcination for 6-8h.

[0015] Furthermore, the preparation method of heat-resistant aggregate is: adding modified silicon carbide fiber to a hot isostatic pressing furnace, raising the temperature of the hot isostatic pressing device to 1500-1800°C, and the pressure to 200-300MPa, and after high temperature and high pressure treatment for 4-6 hours, a heat-resistant aggregate precursor is obtained.

[0016] Reaction principle: Under high temperature, atoms in the grain boundaries move and rearrange, which promotes the bonding between particles and reduces the porosity in the material; under high pressure, particles in the material undergo microscopic plastic deformation, and the particles rearrange themselves under high temperature and high pressure conditions and fill into the pores. This plastic deformation not only eliminates the porosity of the material, but also the pores in the material gradually close under the action of isostatic pressure. As the temperature and pressure increase, the gas in the pores will be compressed or discharged, and the pore walls will collapse or weld, eventually making the interior of the material densified.

[0017] Further, the preparation method of the modified silicon carbide fiber is:

[0018] B1. Add 2-vinyl-4,6-diethyl-1,3,5-triazine, 1,1,3,3-tetramethyldisiloxane, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene into a reaction kettle, raise the temperature of the reaction kettle to 80-90° C., keep the temperature for reaction for 3-5 hours, and post-treat to obtain modified polysilane;

[0019] The reaction equation for preparing modified polysilane is:

[0020]

[0021] Reaction principle for preparing modified polysilane: Under the promotion of high temperature and catalyst, the silicon-hydrogen bonds on 1,1,3,3-tetramethyldisiloxane and the double bond structure on 2-vinyl-4,6-diethyl-1,3,5-triazine continuously undergo silicon-hydrogen addition reaction, eventually forming a tightly cross-linked polymer structure.

[0022] B2, heating and keeping the modified polysilane in the barrel of a melt spinning machine to ensure that the precursor is in a uniform molten state, and stretching and curing after being ejected from the spinning head to obtain a fiber precursor;

[0023] B3. Add the fiber precursor into a tubular furnace and obtain modified silicon carbide fiber through high-temperature calcination.

[0024] The reaction principle of preparing modified silicon carbide fiber: In the temperature range of 700-900℃, the groups in the fiber precursor begin to decompose, releasing volatile substances, leaving inorganic components. When heating to 1200-1500℃, the remaining inorganic skeleton undergoes further heat treatment. At this time, carbon-silicon bonds are gradually formed, completing the transformation process of silicon carbide.

[0025] Further, in step B1, the amount ratio of 2-vinyl-4,6-diethyl-1,3,5-triazine, 1,1,3,3-tetramethyldisiloxane, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene is 5-8g:3-5g:0.5-0.8g:30-40mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction solution is placed in a rotary evaporator at a temperature of 80-100°C, and evaporated until no liquid is produced to obtain modified polysilane; in step B2, the barrel heating temperature is 250-300°C, the spinning head diameter is 50-100μm, and the stretching ratio is 1:5-1 0, the spinning speed is controlled at 10-50m / min, the curing operation is: placing the material in a cooling channel, introducing nitrogen into the cooling channel, the nitrogen flow rate is 5-8m / s, the nitrogen amount is 100-500mL / min, and cooling to room temperature to obtain a fiber precursor; in step B3, the high-temperature calcination operation is: introducing nitrogen protection into a tubular furnace, the tubular furnace is heated to 700-900℃ at a heating rate of 5-8℃, and after heat treatment for 1-2h, it is continued to be heated to 1200-1500℃ at a heating rate of 5-8℃, and after heat treatment for 1-2h, it is cooled to room temperature in a nitrogen atmosphere to obtain a modified silicon carbide fiber.

[0026] Furthermore, the preparation method of the inorganic adhesive comprises the following steps:

[0027] C1. Add tetraethoxysilane and ethanol into a reaction kettle and stir. After the temperature of the reaction kettle rises to 50-60° C., add 10-15 wt % phosphoric acid aqueous solution into the reaction kettle, control the pH value of the solution to 10-12, keep warm and stir for 6-8 hours, and obtain silica gel after the reaction is completed;

[0028] The reaction principle for preparing silica gel is as follows: under alkaline conditions, tetraethoxysilane is hydrolyzed to generate silanol groups, which then undergo condensation to further form a spatial network structure to obtain silica gel.

[0029] C2. Add the silicone gel into the reactor and stir. During the stirring process, add 20-30wt% phosphoric acid aqueous solution into the reactor to adjust the pH of the system to 2-4. After continuing to stir for 1-2 hours, add alumina powder into the reactor and continue to stir for 3-4 hours. After post-treatment, obtain the inorganic adhesive.

[0030] The principle of preparing inorganic adhesives is as follows: under alkaline conditions, the hydrolysis rate of tetraethoxysilane is too fast, resulting in the formation of larger pores in the resulting gel structure, and local gelation leads to an uneven or loose network structure. After secondary hydrolysis filling in an acidic environment and further cross-linking of the preliminary network generated under alkaline conditions, the gel structure becomes denser, and the phosphate groups are cross-linked with the active functional groups on the surface of the gel. At the same time, alumina reacts with phosphoric acid, and the resulting aluminum phosphate can be embedded in the silica gel network in the form of grafting or composite, thereby forming a silica-aluminum phosphate composite structure, and finally the inorganic adhesive is prepared.

[0031] Furthermore, in step C1, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of tetraethoxysilane and ethanol is 10-12mL:30-40mL; in step C2, the dosage ratio of silica gel and alumina powder is 8-10g:2-3g, and the post-treatment includes: after the reaction is completed, the reactant system is adjusted to neutral using sodium bicarbonate, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction solution is distilled under reduced pressure until no liquid is extracted, and then washed with ethanol and deionized water for 3-5 times, and naturally air-dried to obtain an inorganic adhesive.

[0032] A method for preparing refractory high-strength coke oven mud comprises the following steps:

[0033] S1. Adding modified high temperature clay, heat-resistant aggregate, silica sand and steel fiber into a mixer and mixing them evenly to obtain a mixture;

[0034] S2. Add the mixture into a twin-screw extruder, gradually add an inorganic adhesive and water glass into the mixture during stirring, set the pressure of the twin-screw extruder to 50-80 bar, and obtain coke oven mud after twin-screw extrusion.

[0035] The present invention has the following beneficial effects:

[0036] 1. The present invention ensures the compatibility between systems by preparing silicon-based modified high-temperature clay, heat-resistant aggregate and inorganic adhesive, and the stability of the silicon-oxygen structure provides the system with extremely excellent high-temperature resistance and acid resistance. The heat-resistant aggregate obtained after atomic rearrangement of the modified silicon carbide fiber after hot isostatic pressing has an extremely excellent spatial structure, which significantly improves the mechanical strength of the material as a skeleton. The inorganic adhesive introduces an aluminum phosphate structure in the process of preparing silica gel by hydrolysis of the silicon source, so that it has excellent high-temperature bonding ability. The three are combined with auxiliary materials to obtain a fire-resistant, high-strength, low-acid, and thermal shock-resistant coke oven mud.

[0037] 2. In the process of preparing coal coke oven mud, the present invention prepares a modified polysilane, and the organic chain segments are decomposed by high-temperature treatment to form a silicon carbide skeleton. Compared with the silicon carbide structure obtained by high-temperature treatment of long-chain silane, the internal melamine is carbonized during the formation of the silicon carbide chain segments. After hot isostatic pressing, atomic migration occurs on the surface of the resulting modified silicon carbide structure and the carbon particles in the material undergo microscopic plastic deformation. The particles are rearranged under high temperature and high pressure conditions and filled into the pores, thereby densifying the modified silicon carbide fibers to obtain heat-resistant aggregate. As a skeleton structure after the mud is solidified, it offsets part of the internal stress and plays a bonding role in the process of internal fracture, thereby significantly improving the room temperature flexural strength and the post-thermal shock flexural strength.

[0038] 3. In the process of preparing coke oven mud, the present invention prepares an inorganic adhesive. In the process of producing silicone rubber through hydrolysis of silicon source, the generated aluminum phosphate can be embedded in the silica gel network in the form of grafting or composite, so as to obtain a silica-aluminum phosphate composite structure, wherein the silica gel component enhances the cross-linking ability of the remaining silicon-based modified high-temperature clay and heat-resistant aggregate, and its aluminum phosphate structure forms a stable structure cross-linked by chemical bonds with silica at high temperature, further enhancing the adhesion ability of the inorganic adhesive, wherein a large amount of silicon-oxygen stable structure significantly reduces the thermal permanent linear change rate of the coke oven mud, and compared with the organic adhesive, the inorganic adhesive will not be pyrolyzed at high temperature, thereby reducing the voids generated by the gas escape generated by the pyrolysis of the raw materials during the mud solidification process, so that the material has excellent thermal shock resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is a SEM image of the modified silicon carbide fiber prepared by the present invention;

[0041] Figure 2 This is a SEM image of the heat-resistant aggregate prepared in the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The ultrafine calcined kaolin used in the present invention was purchased from Shandong Qiyi Chemical Technology Co., Ltd., with a mesh size of 6000 mesh; the silicone particles used in the present invention were purchased from Hangzhou Kaijie Plastic Technology Co., Ltd., with a product number of KJ-A01.

[0044] Example 1

[0045] This embodiment provides a method for preparing refractory high-strength coke oven mud, comprising the following steps:

[0046] S1. Preparation of modified high temperature clay

[0047] Weigh: 75.0g ultrafine calcined kaolin, 16.0g silicon powder and 6.4g silicone particles, mix them evenly and press them into shape. After natural air drying for 1h, place them in an oven and bake them for 2h at a temperature of 100°C to obtain prefabricated clay;

[0048] The prefabricated clay was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 1400°C at a heating rate of 5°C / min, and the temperature was kept and calcined for 6 hours to obtain modified high-temperature clay.

[0049] S2. Preparation of heat-resistant aggregate

[0050] Weigh: 12.0 g 2-vinyl-4,6-diethyl-1,3,5-triazine, 8.0 g 1,1,3,3-tetramethyldisiloxane, 1.2 g bis(dimethyl(vinyl)silyl)platinum dihydride and 70.0 mL toluene, add into a reactor, raise the temperature of the reactor to 80° C., keep warm for 3 hours, after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, place the reaction solution in a rotary evaporator at 80° C., evaporate until no liquid is produced, and obtain modified polysilane;

[0051] The modified polysilane was heated and kept warm in the barrel of the melt spinning machine. The barrel heating temperature was 250°C to ensure that the precursor was in a uniform molten state. After being ejected from the spinning head, it was stretched. The diameter of the spinning head was 50 μm, the stretching ratio was 1:5, and the spinning speed was controlled at 10 m / min. After the spinning was completed, the material was placed in a cooling channel, and nitrogen was introduced into the cooling channel. The flow rate of nitrogen was 5 m / s and the amount of nitrogen was 100 mL / min. After cooling to room temperature, a fiber precursor was obtained.

[0052] The fiber precursor was added into a tubular furnace, and nitrogen was introduced into the tubular furnace for protection. The temperature of the tubular furnace was increased to 700°C at a rate of 5°C / min, and the temperature was kept at this temperature for 1 hour. The temperature was then increased to 1200°C at a rate of 5°C / min, and the temperature was kept at this temperature for 1 hour. The fiber was then cooled to room temperature under a nitrogen atmosphere to obtain modified silicon carbide fiber.

[0053] The modified silicon carbide fiber is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1500°C, and the pressure is increased to 200MPa. After high temperature and high pressure treatment for 4 hours, a heat-resistant aggregate precursor is obtained.

[0054] S3. Preparation of inorganic adhesive

[0055] Weigh: 20.0 mL of tetraethoxysilane and 60.0 mL of ethanol are added to a reactor and stirred. After the temperature of the reactor rises to 50° C., 10 wt % phosphoric acid aqueous solution is added dropwise to the reactor, the pH of the solution is controlled to be 10, and the mixture is stirred for 6 hours at the same temperature. After the reaction is completed, a silica gel is obtained;

[0056] Add silica gel into the reactor and stir. During the stirring process, add 20 wt % phosphoric acid aqueous solution into the reactor to adjust the pH of the system to 4. After continuing to stir for 1 hour, add alumina powder into the reactor and continue to stir for 3 hours. After the reaction is completed, use sodium bicarbonate to adjust the reactant system to neutrality. Add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, distill under reduced pressure until no liquid is extracted, wash with ethanol and deionized water for 3 times, and air-dry naturally to obtain an inorganic adhesive.

[0057] S4. Preparation of coke oven slurry

[0058] Weigh 36.0 g of modified high temperature clay, 24.0 g of heat-resistant aggregate, 12.0 g of inorganic adhesive, 16.0 g of silica sand, 12.0 g of water glass and 3.6 g of steel fiber for later use;

[0059] Adding modified high temperature clay, heat-resistant aggregate, silica sand and steel fiber into a mixer and mixing them evenly to obtain a mixture;

[0060] The mixed material is added into a twin-screw extruder, and an inorganic adhesive and water glass are gradually added into the mixed material during stirring. The pressure of the twin-screw extruder is set to 50 bar, and coke oven slurry is obtained after twin-screw extrusion.

[0061] Example 2

[0062] This embodiment provides a method for preparing refractory high-strength coke oven mud, comprising the following steps:

[0063] S1. Preparation of modified high temperature clay

[0064] Weigh: 80.0g ultrafine calcined kaolin, 20.0g silicon powder and 8.0g silicone particles, mix them evenly and press them into shape. After natural air drying for 1h, place them in an oven and bake them for 2h at a temperature of 100°C to obtain prefabricated clay;

[0065] The prefabricated clay was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 1600°C at a heating rate of 5°C / min, and the temperature was kept and calcined for 8 hours to obtain modified high-temperature clay.

[0066] S2. Preparation of heat-resistant aggregate

[0067] Weigh: 12.0 g 2-vinyl-4,6-diethyl-1,3,5-triazine, 7.0 g 1,1,3,3-tetramethyldisiloxane, 1.2 g bis(dimethyl(vinyl)silyl)platinum dihydride and 80 mL toluene, add into a reactor, raise the temperature of the reactor to 90° C., keep warm for 5 hours, after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, place the reaction solution in a rotary evaporator at a temperature of 100° C., evaporate until no liquid is produced, and obtain modified polysilane;

[0068] The modified polysilane was heated and kept warm in the barrel of the melt spinning machine. The barrel heating temperature was 300°C to ensure that the precursor was in a uniform molten state. After being ejected from the spinning head, it was stretched. The diameter of the spinning head was 100 μm, the stretching ratio was 1:10, and the spinning speed was controlled at 50 m / min. After the spinning was completed, the material was placed in a cooling channel, and nitrogen was introduced into the cooling channel. The flow rate of nitrogen was 8 m / s, and the amount of nitrogen was 500 mL / min. After cooling to room temperature, a fiber precursor was obtained;

[0069] The fiber precursor was added into a tubular furnace, and nitrogen was introduced into the tubular furnace for protection. The temperature of the tubular furnace was increased to 900°C at a heating rate of 8°C / min, and the temperature was kept at this temperature for 2 hours. The temperature was then increased to 1500°C at a heating rate of 8°C / min, and the temperature was kept at this temperature for 2 hours. The fiber was then cooled to room temperature under a nitrogen atmosphere to obtain modified silicon carbide fiber.

[0070] The modified silicon carbide fiber is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1800°C, and the pressure is increased to 300MPa. After high temperature and high pressure treatment for 6 hours, a heat-resistant aggregate precursor is obtained.

[0071] S3. Preparation of inorganic adhesive

[0072] Weigh: 24.0 mL of tetraethoxysilane and 80.0 mL of ethanol are added to a reaction kettle and stirred. After the temperature of the reaction kettle rises to 60° C., 15.0 wt % phosphoric acid aqueous solution is added dropwise to the reaction kettle, the pH of the solution is controlled to be 12, and the mixture is stirred for 8 hours at the same temperature. After the reaction is completed, a silica gel is obtained;

[0073] Add silica gel to the reactor and stir. During the stirring process, add 30.0wt% phosphoric acid aqueous solution to the reactor to adjust the pH of the system to 2. After continuing to stir for 2 hours, add alumina powder to the reactor and continue to stir for 4 hours. After the reaction is completed, use sodium bicarbonate to adjust the reactant system to neutrality, add the reaction solution to a rotary evaporator with a water bath temperature of 100°C, distill under reduced pressure until no liquid is extracted, wash with ethanol and deionized water 5 times, and air-dry naturally to obtain an inorganic adhesive.

[0074] S4. Preparation of coke oven slurry

[0075] Weigh 42.0 g of modified high temperature clay, 36.0 g of heat-resistant aggregate, 12.0 g of inorganic adhesive, 20.0 g of silica sand, 15.0 g of water glass and 3.0 g of steel fiber for later use;

[0076] Adding modified high temperature clay, heat-resistant aggregate, silica sand and steel fiber into a mixer and mixing them evenly to obtain a mixture;

[0077] The mixed material is added into a twin-screw extruder, and an inorganic adhesive and water glass are gradually added into the mixed material during the stirring process. The pressure of the twin-screw extruder is set to 80 bar, and the coke oven mud is obtained after the twin-screw extrusion.

[0078] Example 3

[0079] This embodiment provides a method for preparing refractory high-strength coke oven mud, comprising the following steps:

[0080] S1. Preparation of modified high temperature clay

[0081] Weigh: 78.0g ultrafine calcined kaolin, 18.0g silicon powder and 6.0g silicone particles, mix them evenly and press them into shape. After natural air drying for 2h, place them in an oven and bake them for 3h at a temperature of 125°C to obtain prefabricated clay;

[0082] The prefabricated clay was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 1500°C at a heating rate of 5°C / min, and the temperature was kept and calcined for 7 hours to obtain modified high-temperature clay.

[0083] S2. Preparation of heat-resistant aggregate

[0084] Weigh: 16.0 g 2-vinyl-4,6-diethyl-1,3,5-triazine, 8.0 g 1,1,3,3-tetramethyldisiloxane, 1.6 g bis(dimethyl(vinyl)silyl)platinum dihydride and 80.0 mL toluene, add into a reactor, raise the temperature of the reactor to 90° C., keep warm for 4 hours, after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, place the reaction solution in a rotary evaporator at a temperature of 90° C., evaporate until no liquid is produced, and obtain modified polysilane;

[0085] The modified polysilane is heated and kept warm in the barrel of the melt spinning machine. The barrel heating temperature is 275°C to ensure that the precursor is in a uniform molten state. After being ejected from the spinning head, it is stretched. The diameter of the spinning head is 75 μm, the stretching ratio is 1:5-10, and the spinning speed is controlled at 30 m / min. After the spinning is completed, the material is placed in a cooling channel, and nitrogen is introduced into the cooling channel. The flow rate of nitrogen is 6 m / s, and the amount of nitrogen is 300 mL / min. After cooling to room temperature, a fiber precursor is obtained;

[0086] The fiber precursor was added into a tubular furnace, and nitrogen was introduced into the tubular furnace for protection. The temperature of the tubular furnace was increased to 800°C at a heating rate of 6°C / min, and the temperature was kept at this temperature for 2 hours. The temperature was then increased to 1300°C at a heating rate of 6°C / min, and the temperature was kept at this temperature for 2 hours. The fiber was then cooled to room temperature in a nitrogen atmosphere to obtain modified silicon carbide fiber.

[0087] The modified silicon carbide fiber is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1600°C, and the pressure is increased to 250MPa. After high temperature and high pressure treatment for 2 hours, a heat-resistant aggregate precursor is obtained.

[0088] S3. Preparation of inorganic adhesive

[0089] Weigh: 24.0 mL of tetraethoxysilane and 80.0 mL of ethanol are added to a reaction kettle and stirred. After the temperature of the reaction kettle rises to 55° C., 12.0 wt % phosphoric acid aqueous solution is added dropwise to the reaction kettle, the pH of the solution is controlled to be 11, and the mixture is stirred for 7 hours at the same temperature. After the reaction is completed, a silica gel is obtained;

[0090] Add silica gel into the reactor and stir. During the stirring process, add 24.0wt% phosphoric acid aqueous solution into the reactor to adjust the pH of the system to 3. After continuing to stir for 2 hours, add alumina powder into the reactor and continue to stir for 3 hours. After the reaction is completed, use sodium bicarbonate to adjust the reactant system to neutrality. Add the reaction solution into a rotary evaporator with a water bath temperature of 90°C, distill under reduced pressure until no liquid is extracted, wash with ethanol and deionized water for 4 times, and air-dry naturally to obtain an inorganic adhesive.

[0091] S4. Preparation of coke oven slurry

[0092] Weigh 48.0 g of modified high temperature clay, 36.0 g of heat-resistant aggregate, 12.0 g of inorganic adhesive, 18.0 g of silica sand, 12.0 g of water glass and 4.0 g of steel fiber for later use;

[0093] Adding modified high temperature clay, heat-resistant aggregate, silica sand and steel fiber into a mixer and mixing them evenly to obtain a mixture;

[0094] The mixed material is added into a twin-screw extruder, and an inorganic adhesive and water glass are gradually added into the mixed material during stirring. The pressure of the twin-screw extruder is set to 60 bar, and coke oven mud is obtained after twin-screw extrusion.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 3 is that step S1 is omitted, and in step S4, kaolin is used in an equal amount to replace the modified high-temperature clay.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 3 is that step S2 is eliminated, and in step S4, an equal amount of glass fiber is used to replace the heat-resistant aggregate.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 3 is that step S3 is eliminated, and in step S4, an equal amount of phenolic resin is used to replace the inorganic adhesive.

[0101] Performance Testing:

[0102] Referring to the standard JC / T 499-2013 "Steel Fiber Reinforced Refractory Castables", the room temperature flexural strength, room temperature compressive strength, flexural strength after 5 cycles of rapid cooling and rapid heating at 1100°C-room temperature water, and permanent linear change rate after heating of the coke oven slurries prepared in Examples 1-3 and Comparative Examples 1-3 after solidification were tested;

[0103] The acid resistance of the coke oven slurry prepared in Examples 1-3 and Comparative Examples 1-3 after solidification was tested with reference to the standard GB / T 17601-2023 "Test method for acid resistance of refractory materials";

[0104] See Table 1 for specific data.

[0105] Table 1-Performance test table of each sample

[0106]

[0107]

[0108] Data Analysis:

[0109] By referring to the data in Table 1 above, the coke oven slurry prepared by the present invention has a room temperature flexural strength of 15.2 MPa, a room temperature compressive strength of 98 MPa, a flexural strength after thermal shock of 9.2 MPa, a heating permanent linear change rate of 0.2%, and an acid resistance of 99.8%, which shows that:

[0110] In the process of preparing a coke oven slurry, the present invention first modifies kaolin to obtain a silicon-philic modified high-temperature clay, improves its high-temperature resistance and compatibility with heat-resistant aggregates and inorganic adhesives, and prepares a modified polysilane through reaction. After high-temperature treatment, its organic matter is decomposed to form a silicon carbide skeleton, the internal melamine is carbonized, and nitrogen groups are introduced to modify the surface of the silicon carbide skeleton. After the generated carbon structure is subjected to hot isostatic pressing, atomic migration occurs on the surface and particles in the material undergo microscopic plastic deformation, such as Figure 1 As shown, the particles are rearranged under high temperature and high pressure conditions and filled into the pores, making the modified silicon carbide fibers dense and obtaining heat-resistant aggregates. As the skeleton structure after the slurry is solidified, the room temperature flexural strength and the flexural strength after thermal shock are significantly improved.

[0111] An inorganic adhesive is further prepared. During the hydrolysis process, the aluminum phosphate generated can be embedded in the silica gel network in the form of grafting or composite, obtaining a silica-aluminum phosphate composite structure, wherein the silica gel component enhances the cross-linking ability of the remaining silicon-based modified high-temperature clay and heat-resistant aggregates, and its aluminum phosphate structure forms a stable structure cross-linked by chemical bonds with silica at high temperature, further enhancing the adhesion ability of the inorganic adhesive. The large amount of silicon-oxygen stable structure significantly reduces the thermal permanent linear change rate of the coke oven mud, and compared with the organic adhesive, the inorganic adhesive will not pyrolyze at high temperature, thereby reducing the voids generated by the escape of gas generated by the pyrolysis of the raw materials during the mud solidification process, making the material excellent in thermal shock resistance, and finally preparing a fire-resistant, high-strength, low-carbon, acid-resistant and thermal shock-resistant coke oven mud.

[0112] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0113] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0114] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A refractory high-strength coke oven mud, characterized in that: The raw material composition includes the following parts by weight: 30-50 parts of modified high temperature clay, 20-40 parts of heat-resistant aggregate, 5-15 parts of inorganic adhesive, 10-25 parts of silica sand, 5-15 parts of water glass and 1-5 parts of steel fiber; The preparation method of modified high temperature clay comprises the following steps: A1. Mix ultrafine calcined kaolin, silicon micropowder and silicone particles evenly and press them into shape. After natural air drying for 1-2 hours, place them in an oven and bake them for 2-4 hours to obtain prefabricated clay, wherein the amount ratio of ultrafine calcined kaolin, silicon micropowder and silicone particles is 75-80g:15-20g:5-8g, and the temperature of the oven is 100-150°C; A2. Add the prefabricated clay into a tubular furnace, introduce nitrogen protection, heat the tubular furnace to 1400-1600°C at a heating rate of 5°C / min, and calcine for 6-8h to obtain modified high-temperature clay; The preparation method of heat-resistant aggregate is as follows: adding modified silicon carbide fiber into a hot isostatic pressing furnace, raising the temperature of the hot isostatic pressing device to 1500-1800°C, and the pressure to 200-300MPa, and after high temperature and high pressure treatment for 4-6h, heat-resistant aggregate is obtained; The preparation method of modified silicon carbide fiber is: B1. Add 2-vinyl-4,6-diethyl-1,3,5-triazine, 1,1,3,3-tetramethyldisiloxane, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene into a reaction kettle, raise the temperature of the reaction kettle to 80-90° C., keep the temperature for reaction for 3-5 hours, and post-treat to obtain modified polysilane; B2, heating and keeping the modified polysilane in the barrel of a melt spinning machine to ensure that the precursor is in a uniform molten state, and stretching and curing after being ejected from the spinning head to obtain a fiber precursor; B3, adding the fiber precursor into a tubular furnace, introducing nitrogen protection into the tubular furnace, heating the tubular furnace to 700-900°C at a heating rate of 5-8°C, keeping the temperature for 1-2 hours, and then continuing to heat the temperature to 1200-1500°C at a heating rate of 5-8°C, keeping the temperature for 1-2 hours, and cooling to room temperature under a nitrogen atmosphere to obtain modified silicon carbide fiber; The preparation method of the inorganic adhesive comprises the following steps: C1. Add tetraethoxysilane and ethanol into a reaction kettle and stir. After the temperature of the reaction kettle rises to 50-60° C., add 10-15 wt % phosphoric acid aqueous solution into the reaction kettle, control the pH value of the solution to 10-12, keep warm and stir for 6-8 hours, and obtain silica gel after the reaction is completed; C2. Add the silicone gel into the reactor and stir. During the stirring process, add 20-30wt% phosphoric acid aqueous solution into the reactor to adjust the pH of the system to 2-4. After continuing to stir for 1-2 hours, add alumina powder into the reactor and continue to stir for 3-4 hours. After post-treatment, obtain the inorganic adhesive.

2. The refractory high-strength coke oven mud according to claim 1, characterized in that: In step B1, the amount ratio of 2-vinyl-4,6-diethyl-1,3,5-triazine, 1,1,3,3-tetramethyldisiloxane, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene is 5-8g:3-5g:0.5-0.8g:30-40mL; in step B2, the barrel heating temperature is 250-300°C, the spinning head diameter is 50-100μm, the stretching ratio is 1:5-10, and the spinning speed is controlled at 10-50m / min.

3. The refractory high-strength coke oven mud according to claim 1, characterized in that: In step C1, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of tetraethoxysilane to ethanol is 10-12mL:30-40mL; in step C2, the dosage ratio of silica gel to alumina powder is 8-10g:2-3g, and the post-treatment includes: after the reaction is completed, the reactant system is adjusted to neutrality using sodium bicarbonate, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction solution is distilled under reduced pressure until no liquid is extracted, and then washed with ethanol and deionized water for 3-5 times, and naturally air-dried to obtain an inorganic adhesive.

4. The method for preparing a refractory high-strength coke oven mud according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Adding modified high temperature clay, heat-resistant aggregate, silica sand and steel fiber into a mixer and mixing them evenly to obtain a mixture; S2. Add the mixture into a twin-screw extruder, gradually add an inorganic adhesive and water glass into the mixture during stirring, set the pressure of the twin-screw extruder to 50-80 bar, and obtain coke oven mud after twin-screw extrusion.

Citation Information

Patent Citations

  • High strength coke-oven mortar

    CN85109463A

  • Prefabricated blocky refractory material for coke oven and preparation method of prefabricated blocky refractory material

    CN118851785A

  • Heat-resistant component and manufacturing method therefor

    JP2019172534A